Dispositional Mindfulness as Internal Resource to Optimize Mental Health at Work - Dhevy Puswiartika; Bau Ratu; Rosmala Nur (Journal of The Community Development in Asia, 2025)
Mental health in the workplace is essential because it can affect employees' performance and productivity. One effective strategy to maintain mental health in the workplace is developing dispositional mindfulness in employees. This study aimed to describe dispositional mindfulness as an internal resource of employees in a railway transportation service provider in Jakarta, Indonesia. The study highlights mindfulness as a dispositional trait influencing cognitive, emotional, and behavioral functions, enhancing stress management, work performance, relationships, and overall well-being. The authors used a survey method to distribute the Dispositional Mindfulness at Work Scale to 357 employees in supervisory positions through quota sampling. Data analysis, conducted using SPSS 21.0, revealed that respondents generally exhibited strong dispositional mindfulness, with significant differences based on age and education level. Among the components of mindfulness, awareness emerged as the dominant trait, followed by acceptance, attention, and present focus. These findings suggest that management can implement mindfulness programs to enhance work performance and service quality. This study contributes to the literature on mindfulness in organizational settings, particularly within the railway transportation sector.